2019
DOI: 10.1111/aogs.13773
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in women with cerebral palsy: A nationwide population‐based cohort study

Abstract: Introduction Cerebral palsy (CP) is a lifelong disorder with a high rate of comorbidities and complications. We hypothesized that women with CP are at increased risk of adverse pregnancy outcome. Material and methods In this nationwide population‐based cohort study 1997‐2011, we examined the outcome of 770 births in women with CP vs 1 247 408 births in women without a CP diagnosis using the Swedish Medical Birth Register. We used unconditional logistic regression, adjusting for maternal age, smoking, parity, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
2
9
0
1
Order By: Relevance
“…Based on previous analysis, autistic women in our sample are more educated and likely to be married as compared to other IDD groups 10 and this socioeconomic advantage compared to other IDD groups may lead to relatively better outcomes. Our findings for infants of mothers with intellectual disability or cerebral palsy were aligned with past work on those specific conditions 43,44 . Consistently poor outcomes across IDD‐type may indicate that these women face some similar social and health disparities.…”
Section: Resultssupporting
confidence: 78%
“…Based on previous analysis, autistic women in our sample are more educated and likely to be married as compared to other IDD groups 10 and this socioeconomic advantage compared to other IDD groups may lead to relatively better outcomes. Our findings for infants of mothers with intellectual disability or cerebral palsy were aligned with past work on those specific conditions 43,44 . Consistently poor outcomes across IDD‐type may indicate that these women face some similar social and health disparities.…”
Section: Resultssupporting
confidence: 78%
“…In addition, women with intellectual disability may face increased barriers when navigating the health care service system [ 31 ], especially for pregnancy care [ 9 ]. The increased risk for caesarean delivery for women with cerebral palsy may be due to chronic pain, pelvic abnormalities, spasticity, and other physical disabilities [ 12 ]. Because of the approximate 4:1 male to female sex ratio in autism [ 32 ], and temporal cohort effects [ 3 ], we saw relatively fewer births to women on the autism spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Further, little is known about pregnancy outcomes among specific IDD types (e.g. cerebral palsy, intellectual disability) and more work is needed, as there may be different associations with outcomes based on phenotypic and genetic presentation of the IDD [ 12 ]. Adults of color with disabilities often face compounded disparity that leads to excess poor health [ 13 , 14 ], but literature is lacking surrounding pregnancy in women of color with IDD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…They tend to lack the knowledge and experience to treat disabled women who are pregnant and expect these pregnancies to be associated with complications and poor outcomes (Mitra et al, 2016). The few studies focusing on women with CP and pregnancy found that women experience a decline in physical mobility and function after pregnancy, yet there was no evidence of specialist accommodations in place for these women, either before, during or after childbirth (Hayward et al, 2017;Sundelin et al, 2020).…”
Section: Backg Rou N Dmentioning
confidence: 99%